RANCANG BANGUN SISTEM INFORMASI PENERIMAAN MAHASISWA BARU BERBASIS WEB DI SEKOLAH TINGGI KEGURUAN ILMU PENDIDIKAN PARACENDEKIA NAHDLATUL WATHAN SUMBAWA - Muhammad Dian Fajri; Wirentake; M. Julkarnain (Jurnal Informatika Teknologi dan Sains, 2020)
STKIP Paracendekia NW Sumbawa is an educational institution that deals in English education and mathematics education. STKIP Paracendekia NW Sumbawa organizes new student admissions every year. In organizing the admission of new students, STKIP Paracendekia NW Sumbawa still uses a manual system that is by recording all registrants using books and registration forms are still stored in a cupboard. This makes it difficult for the organizing committee to manage data, which data will change from time to time. The solution to the problems that are happening at STKIP Paracendekia NW Sumbawa is to build a Web-Based New Student Admission Information System at STKIP Paracendekia NW Sumbawa. This system was developed using the PHP programming language by using the CodeIgniter and MysSql Framework as a database. The method used in building this system is to use the waterfall method. This system is expected to simplify and speed up the data management process for prospective new students.